Prevalence of colistin heteroresistance in carbapenem-resistant Pseudomonas aeruginosa and association with clinical outcomes in patients: an observational study. (16th December 2021) - Howard-Anderson, Jessica; Davis, Michelle; Page, Alexander M; Bower, Chris W; Smith, Gillian; Jacob, Jesse T; Andersson, Dan I; Weiss, David S; Satola, Sarah W
Abstract: Objectives: To describe the prevalence of colistin heteroresistance in carbapenem-resistant Pseudomonas aeruginosa (CRPA) and evaluate the association with clinical outcomes. Methods: Colistin heteroresistance was evaluated in CRPA isolates collected from patients without cystic fibrosis in Atlanta, Georgia, USA using two definitions: HR1, growth at 4 and 8 mg/L of colistin at a frequency ≥1 × 10 −6 the main population; and HR2, growth at a colistin concentration ≥8× the MIC of the main population at a frequency ≥1 × 10 −7 . A modified population analysis profile (mPAP) technique was compared with reference PAP for detecting heteroresistance. For adults hospitalized at the time of or within 1 week of CRPA culture, multivariable logistic regression estimated the association between heteroresistance and 90 day mortality. Results: Of 143 colistin-susceptible CRPA isolates, 8 (6%) met the HR1 definition and 37 (26%) met the HR2 definition. Compared with the reference PAP, mPAP had a sensitivity and specificity of 50% and 100% for HR1 and 32% and 99% for HR2. Of 82 hospitalized patients, 45 (56%) were male and the median age was 63 years (IQR 49–73). Heteroresistance was not associated with 90 day mortality using HR1 (0% in heteroresistant versus 22% in non-heteroresistant group; P  = 0.6) or HR2 (12% in heteroresistant versus 24% in non-heteroresistant group; P  = 0.4; adjusted OR 0.8; 95% CI 0.2–3.4). Conclusions: Colistin heteroresistance was identified in up to 26% of patients with CRPA in our sample, although the prevalence varied depending on the definition. We did not observe an apparent association between colistin heteroresistance and 90 day mortality.